(untitled) - Nwogugu, Michael C. I.; Michael C.I. Nwogugu (Hoboken N.J.)
Essential reading for professional investors, risk managers, regulators, central bankers, and real estate professionals, Risk in the Global Real Estate Market: International Risk Regulation, Mechanism Design, Foreclosures, Title Systems, and REITs takes an international look at the ways in which U.S.-style constitutional laws, financial laws, and real estate laws in various countries affect global economics and risk; and analyzes specific constraints that deter market development such as Asset Liability Matching, inappropriate financial products, land title systems, inefficient constitutions and human biases. The sub-prime mortgage crisis (that began around 2006) and the Global Financial Crisis of 2007 2010 disrupted the economies of various countries and exposed many of the psychological, social, and economic problems inherent in the legal/risk infrastructure for mortgages, land title systems, REITs, securitization, and pensions
Includes bibliographical references and index
Keywords: Real estate business; Risk; Mortgages; Foreclosure; Real estate investment trusts